Tissue-specific transcriptomics and proteomics of a filarial nematode and its Wolbachia endosymbiont. (December 2015) - Luck, Ashley; Anderson, Kathryn; McClung, Colleen; VerBerkmoes, Nathan; Foster, Jeremy; Michalski, Michelle; Slatko, Barton
Abstract Background Filarial nematodes cause debilitating human diseases. While treatable, recent evidence suggests drug resistance is developing, necessitating the development of novel targets and new treatment options. Although transcriptomic and proteomic studies around the nematode life cycle have greatly enhanced our knowledge, whole organism approaches have not provided spatial resolution of gene expression, which can be gained by examining individual tissues. Generally, due to their small size, tissue dissection of human-infecting filarial nematodes remains extremely challenging. However, canine heartworm disease is caused by a closely related and much larger filarial nematode, Dirofilaria immitis . As with many other filarial nematodes, D. immitis containsWolbachia, an obligate bacterial endosymbiont present in the hypodermis and developing oocytes within the uterus. Here, we describe the first concurrent tissue-specific transcriptomic and proteomic profiling of a filarial nematode (D. immitis) and itsWolbachia (w Di) in order to better understand tissue functions and identify tissue-specific antigens that may be used for the development of new diagnostic and therapeutic tools. Methods AdultD. immitis worms were dissected into female body wall (FBW), female uterus (FU), female intestine (FI), female head (FH), male body wall (MBW), male testis (MT), male intestine (MI), male head (MH) and 10.1186/s12864-015-2083-2 male spicule (MS) and used to prepare transcriptomic and proteomic libraries. Results Transcriptomic and proteomic analysis of severalD. immitis tissues identified many biological functions enriched within certain tissues. Hierarchical clustering of theD. immitis tissue transcriptomes, along with the recently published whole-worm adult male and femaleD. immitis transcriptomes, revealed that the whole-worm transcriptome is typically dominated by transcripts originating from reproductive tissue. The uterus appeared to have the most variable transcriptome, possibly due to age. Although many functions are shared between the reproductive tissues, the most significant differences in gene expression were observed between the uterus and testis. Interestingly, w Di gene expression in the male and female body wall is fairly similar, yet slightly different to that ofWolbachia gene expression in the uterus. Proteomic methods verified 32 % of the predictedD. immitis proteome, including over 700 hypothetical proteins ofD. immitis . Of note, hypothetical proteins were among some of the most abundantWolbachia proteins identified, which may fulfill some important yet still uncharacterized biological function. Conclusions The spatial resolution gained from this parallel transcriptomic and proteomic analysis adds to our understanding of filarial biology and serves as a resource with which to develop future therapeutic strategies against filarial nematodes and theirWolbachia endosymbionts.